The Influence of Endorser Credibility, Brand Image, and Perceived Value on Customer Satisfaction Mediated by Brand Trust (Study of Jafra Consumers in Jakarta - Raditia Nurcahya; Aam Bastaman (Quantitative Economics and Management Studies, 2024)
This study aimed to determine the effects of Endorser Credibility, Brand Image, and Perceived Value on Customer Satisfaction among Jafra consumers in South Jakarta, mediated by Brand Trust, Brand Image, and Perceived Value obtained through distributing questionnaires. The research population consisted of Jafra consumers in South Jakarta, with a sample of 100 people selected using purposive sampling. Data were analyzed using PLS-based SEM. The results indicated that the variables of Endorser Credibility, Brand Image, and Perceived Value had a significant effect on Brand Trust. Furthermore, the results demonstrated that Endorser Credibility, Perceived Value, and Brand Trust significantly influenced Customer Satisfaction. Additionally, it was found that Brand Trust mediated the relationship between Brand Image and Customer Satisfaction, as well as between Perceived Value and Customer Satisfaction.